Antibacterial action of novel zeolite-based compositions depends upon doping with Ag(+) and Сu(2+) cations - N. O. Manko; O. O. Ilkov; O. Yu. Klyuchivska; V. O. Vasylechko; V. V. Sydorchuk; N. P. Kovalska; O. I. Kostiv; S. R. Bagday; A. V. Zelinskiy; O. M. Gromyko; N. V. Skrypchenko; Yа. M. Kalychak; et al. (The Ukrainian Biochemical Journal)
Recently, there is a growing interest to exploration of sorption and catalytic properties of solid nanomaterials, in particular natural zeolites, as well as to study of their antimicrobial effects with the aim of potential using them as a principal component of disinfection and degassing remedies. The purpose of this work was to study the antimicrobial action of compositions based on the Transcarpathian clinoptilolite (CL) doped with Ag+ and Сu2+ cations or Ag microparticles (MPs). These compositions were subjected to mechanochemical modification in ethanol medium and with the addition of plant (Actinidia arguta) extract used as an antioxidant. Mechanochemical treatment (MChT) of all forms of CL MPs led to their grinding which caused better contact of CL with bacterial cells, while an increased content of larger pores improved their access to the active sites on the surface of the CL MPs. Treatment of CL samples with metallic silver used as a dopant with the help of the extract of Actinidia arguta plant did not increase the antibacterial activity regardless of treatment time. Treatment of AgNO3 with ethanol slightly increased the antibacterial action of the CL MPs towards Gram-positive bacteria and decreased it towards Gram-negative bacteria. The CL samples doped with copper and treated with ethanol and plant (Actinidia arguta) extract demonstrated comparable toxic action towards Bacillus subtilis regardless of grinding conditions. While such a treatment caused a significant decrease in the antibacterial activity towards Staphylococcus aureus and Pseudomonas aeruginosa strains, compared to the action of samples that were not treated with that plant extract. To address the potential biochemical mechanisms of the antibacterial action of the created zeolite-based compositions, their influence on generation of the reactive oxygen species (ROS) was studied using diphenylpicrylhydrazyl (DPH) fluorescent dye. Most versions of the CL composites demonstrated time-dependent antioxidant effect comparable with the effect of the ascorbic acid used as a positive control. Thus, the ROS generation is not the mechanism that is responsible for the antibacterial action of the created CL-based compositions. Probably, that action is explained by the peculiarities of interaction of doped CL microparticles with the surface of the bacterial cells.